A cyclin D1-positive diffuse large B-cell lymphoma of germinal center B-cell-like subtype in the right tonsil: A rare case report. Issue 11 (March 2017) - Jiang, Changrui; Shi, Xiuying; Fan, Chuifeng
Abstract: Introduction: Cyclin D1-positive tumor cells are commonly found in mantle cell lymphoma but they are very rare in diffuse large B-cell lymphoma. Clinical findings/Patient concerns: Here we present a rare case of cyclin D1-positive diffuse large B-cell lymphoma in the right tonsil of a 50-year-old man. Computed tomographic imaging detected a mass, about 2.5 cm × 1.8 cm in size, in the left side of the oropharynx. Diagnoses: Microscopically, the tumor cells were located under the pharyngeal mucosa and diffusely arranged. The tumor cells were large, with marked nuclear atypia. On performing immunohistochemistry, the tumor cells showed diffuse positive staining for CD10, CD20, cyclin D1, and Pax-5, and negative staining for CD3, CD15, CD30, CD56, and CK. Bcl-6 and Mum-1 expression were observed in 60% and 80% of tumor cells, respectively. The tumor Ki67 index was about 60%. Based on these findings, The tumor was diagnosed as a rare cyclin D1-positive diffuse large B-cell lymphoma rather than a mantle cell lymphoma. Conclusion: Cyclin D1-positive large B-cell lymphoma is rare, but as large B-cell lymphoma is a common type of lymphoma, cyclin D1-positive large B-cell lymphoma should be considered a major possibility during differential diagnosis, including in the tonsils.